Exploration of Open Innovation and Entrepreneurship Education Practice Teaching System in Local University Software Engineering Major - Wei Le; Cao Liang; Zhao Qiuyun; Shu Hongping (SHS Web of Conferences, 2023)
Innovation and entrepreneurship education practice teaching is an important part of cultivating talents with innovative spirit and entrepreneurial ability. This paper analyses the problems faced by the current practical teaching system of innovation and entrepreneurship education in local universities in cultivating high-quality characteristic software talents. It also puts forward the concept of open innovation and entrepreneurship education, and is based on the concept of integration of industry and education, and integration of specialization and creation. And with the cultivation of innovation and entrepreneurship spirit as the core, the putative innovation and entrepreneurship education practice teaching system is constructed.The system consists of two modules: in-class practice and extracurricular practice. It contains five practical aspects such as in-class experiment, curriculum design, extracurricular practice, enterprise practice and comprehensive practice. In order to cultivate course-level, project-level, competition-level, enterpriselevel and engineering-level professional practice skills respectively. It also integrates course ideology and politics throughout, realizing the organic integration of value leading, knowledge imparting and ability cultivation.